2018
DOI: 10.1108/ijbpa-11-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swine-waste bio-char on the water absorption characteristics of cement pastes

Abstract: Purpose The purpose of this paper is to investigate the effect of an admixture, Swine-waste Bio-char (SB), on the water absorption characteristics of cement pastes. Design/methodology/approach The effect of SB percentages, heat treatment temperatures, water/binder ratios, and age on the water absorption percentages (WAPs) of SB modified cement pastes were investigated using scanning electron microscopy-energy dispersive spectra, FTIR, Brunauer-Emmett-Teller, and laboratory experiments. Findings The WAPs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The re duc tion in the work a bil ity of mor tar mix tures with the incor po ra tion of biochar as re place ment of the Port land ce ment can be as so ci ated with the higher wa ter ab sorp tion of the biochar which resulted in lim ited wa ter avail able for work a bil ity. Sim i larly, Ofori -Boadu et al [ 133 ] re ported a re duc tion in flow when swine biochar was in cor po rated as a re place ment of Port land ce ment in ce ment pastes. The flu id ity of paste con tain ing 2.5%, 5% and 10% swine biochar as re place ment of Port land ce ment is 20%, 33% and 36% lower than the paste with out biochar.…”
Section: 1 Workabilitymentioning
confidence: 99%
“…The re duc tion in the work a bil ity of mor tar mix tures with the incor po ra tion of biochar as re place ment of the Port land ce ment can be as so ci ated with the higher wa ter ab sorp tion of the biochar which resulted in lim ited wa ter avail able for work a bil ity. Sim i larly, Ofori -Boadu et al [ 133 ] re ported a re duc tion in flow when swine biochar was in cor po rated as a re place ment of Port land ce ment in ce ment pastes. The flu id ity of paste con tain ing 2.5%, 5% and 10% swine biochar as re place ment of Port land ce ment is 20%, 33% and 36% lower than the paste with out biochar.…”
Section: 1 Workabilitymentioning
confidence: 99%
“…The adoption and commercialization of such agricultural waste-modified CBMs would create employment and improve living standards. Therefore, large-scale OPC replacement with agricultural waste materials in CBMs could have structural, environmental and economic benefits (Roy et al , 2017; Gupta et al , 2018a, b; Ofori-Boadu et al , 2018a, b, 2017; Suarez-Riera et al , 2020). However, agricultural wastes are composed of cellulose, hemicellulose and lignin and so labile content makes them unuseable in structures (Phonphuak and Chindaprasirt, 2015; Haiping et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolyzed agro-food waste, coffee powder and hazelnuts shells improve flexural and compression strength, when used as carbon nanoaggregates due to pozzolanic reactivity and nucleation (Retuccia and Ferro, 2016). Ofori-Boadu et al (2018a) note that lower temperature treated swine-manure biochars reduce water absorption in cement pastes as a result of residual hydrophobic surface groups from the tars and oils in raw swine manure.…”
Section: Introductionmentioning
confidence: 99%
“…Construction students who had been engaged in bio-modified concrete research had found the research experience to be very valuable and enhanced their perception about the researcher role. Their research experiences in swine-waste modified cement pastes had led to several publications, presentations, and poster sessions [18][19][20]. Construction students had so much identified with their student researcher role that they shared these research experiences during interviews with potential employers; and in one instance, research experiences had contributed to the attainment of a job offer.…”
Section: Figure 5 Mean Preferred Career Role Scoresmentioning
confidence: 99%